HUKUM ISLAM DI ERA DEMIKRASI: TANTANGAN DAN PELUANG BAGI FORMALISASI POLITIK SYARI'AT ISLAM DI INDONESIA - Nurrohman, Nurrohman (ADDIN, 2015)
ISLAMIC LAW IN THE ERA OF DEMOCRACY. Challenges and Opportunities for a formalization of Islamic Politics in Indonesia: This paper describes the long journey of struggle to include the Islamic teaching into constitution and laws of Indonesia, the challenges faced by some muslims who would establish Islamic teaching through state institutions and the extent to which the opportunities provided by the democracy in Indonesia which can be used by muslims to offer what they consider to be Islamic laws. Attempts to include the Islamic teaching (Shari’ah) in the constitution of the republic of Indonesia appeared before this state is officially declared. Before that, the founders of the state have been arguing about the foundation of the state. Most of them want the basic state of Indonesia is Islam, while others require that the state of Indonesia’s basic is nationalism. The first compromise was reached at the time of the founders of state agreed that the Jakarta Charter which combines elements of nationalism and Islam will be the opening of the country’s constitution.